Internalization of Disciplinary Values Through an Integrated Point System at Pondok Modern Darussalam Gontor, Campus 7, Kalianda - Muhammad Rifkhi Maulana; Agus Pahrudin; Achi Rinaldi; Ali Murtadho (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study examines the strategy of internalizing discipline values through an integrated point system at Pondok Modern Darussalam Gontor Campus 7 Kalianda, South Lampung. The research background involves serious problems related to student discipline, including tardiness, absenteeism, and violations of internal pesantren rules. This study aims to analyze the process of internalizing discipline values, the strategies applied, and the impact of the integrated point system on the formation of students' disciplined character. Using a qualitative approach with a case study method, data were collected through participatory observation, in-depth interviews with caregivers, teachers, OPPM administrators, and students, as well as documentation analysis. The results show that the integrated point system at Gontor Campus 7 is implemented through POACE management functions (Planning, Organizing, Actuating, Controlling, Evaluating) managed by the Modern Pesantren Student Organization (OPPM). The internalization process includes three stages: introduction of rules, habituation, and continuous supervision. Forms of reward include praise, reduction of violation points, and granting of leadership responsibilities, while punishment is educative such as additional tasks, special coaching, and temporary revocation of rights. The impact of this system is proven significant in improving student discipline, reducing the number of violations, and creating a conducive pesantren environment. This study recommends strengthening the socialization of the point system to new students and developing a digital-based system to improve transparency and efficiency.